Appraisal of ICH E14/S7B Q&As adopted in February 2022 using thorough QT/QTc study data for α4-integrin antagonist carotegrast methyl in Japanese healthy subjects - Ryuichi Kambayashi; Ai Goto; Hiroko Izumi-Nakaseko; Ichiro Oikawa; Naoki Ikeda; Kazuki Matsuda; Yoshinori Takei; Akio Matsumoto; Yuji Kumagai; Atsushi Sugiyama (Elsevier, 2022)
We investigated how a lack of placebo control affects the interpretation of results of thorough QT/QTc (TQT) study. Results of TQT study in 48 healthy Japanese subjects assessing the effects of 480 and 960 mg of carotegrast methyl (test drug) and 400 mg of moxifloxacin (positive control) on the time-matched changes in corrected QT from baseline (ΔQTcF) and the placebo-adjusted ΔQTcF (ΔΔQTcF) were analyzed with central-tendency and concentration-response analyses. In central-tendency analysis, moxifloxacin prolonged ΔQTcF and ΔΔQTcF with the largest mean values (90% confidence interval) of 12.1 ms (9.3, 14.8) and 15.4 ms (12.6, 18.1), respectively. Meanwhile, carotegrast methyl hardly altered ΔQTcF and ΔΔQTcF with the largest mean values of 0.8 ms (−2.3, 3.9) and 2.1 ms (−0.7, 4.8) for the low dose, and −0.2 ms (−3.4, 3.0) and 1.6 ms (−0.9, 4.2) for the high dose, respectively. In concentration-response analysis, moxifloxacin attained the estimated mean values for ΔQTcF and ΔΔQTcF of 11.4 ms (8.5, 14.4) and 16.7 ms (14.0, 19.4) at the mean Cmax, whereas carotegrast methyl provided those of −4.6 ms (−7.3, −1.9) and 0.7 ms (−1.4, 2.8), respectively. Thus, lack of placebo control did not influence the interpretation of TQT study with either of the analysis in line with updated E14/S7B Q&As.